2018
DOI: 10.1016/j.cmi.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Low genomic diversity of Legionella pneumophila within clinical specimens

Abstract: ObjectivesLegionella pneumophila is the leading cause of Legionnaires' disease, a severe form of pneumonia acquired from environmental sources. Investigations of both sporadic cases and outbreaks rely mostly on analysis of a single to a few colony pick(s) isolated from each patient. However, because of the lack of data describing diversity within single patients, the optimal number of picks is unknown. Here, we investigated diversity within individual patients using sequence-based typing (SBT) and whole-genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, the inhaled dose compared to the deposited dose is unknown, as is the composition of the Legionella population inside human lungs. One study on ten patients found no to very low within-host diversity [71], an hypothesis confirmed by more studies [72,73]. Other studies, however, found the opposite [38,74], and it is thus likely that within-host diversity depends on the diversity of L. pneumophila in environmental sources, variations in infectious dose, and the duration of infection prior to sampling [71].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the inhaled dose compared to the deposited dose is unknown, as is the composition of the Legionella population inside human lungs. One study on ten patients found no to very low within-host diversity [71], an hypothesis confirmed by more studies [72,73]. Other studies, however, found the opposite [38,74], and it is thus likely that within-host diversity depends on the diversity of L. pneumophila in environmental sources, variations in infectious dose, and the duration of infection prior to sampling [71].…”
Section: Discussionmentioning
confidence: 94%
“…One study on ten patients found no to very low within-host diversity [71], an hypothesis confirmed by more studies [72, 73]. Other studies, however, found the opposite [38, 74], and it is thus likely that within-host diversity depends on the diversity of L. pneumophila in environmental sources, variations in infectious dose, and the duration of infection prior to sampling [71]. While antibiotic resistance does not appear to be a current general concern in the environment, antibiotic resistance to fluoroquinolones has been shown to occur within patients [75].…”
Section: Discussionmentioning
confidence: 99%